M-Learning in Art-Education - Usal, Yelda; Sirin, Atilla (Common Ground Research Networks, 2015)
M-Learning, referring to the use of mobile (or smart) phones, computers, and internet in teaching-learning process, have also had a broad repercussion in art education in Turkey. Because, especially in higher education, the use of these technologies is very common. What imposes the use of mobile technology is that these technologies offer significant opportunities for art education and the potential to provide alternative perspectives. However, the use of mobile technologies in art education depends, above all, on students' perception, awareness, and views on this subject. The goal of this research is to determine the views of candidate teachers at İnönü and Firat Universities in 20142015 academic year on the use of mobile technologies in art education. The research was conducted on 148 teachers. The data were obtained through Likert-type questionnaire. To analyze the data, descriptive statistical techniques were utilized. The findings showed that candidate teachers use internet and mobile (or smart) phones to access information and to research, and that they find them useful for academic achievement and creativity. However, students are not fully aware of the opportunities offered by mobile technologies for art education. They, under the influence of traditional understanding, perceive mobile technologies as a tool rather than as a source or setting. Their awareness in M-Learning is low, and they are not aware of transformation in the form of transition to positivism beyond paradigms taking place on a global scale in education. This case brings into disrepute Turkey's "information society" goal in art education. © 2015 International Journal of Learning and Teaching. All Rights Reserved.
Keywords: art education; internet in art education; m-learning; mobile (or smart) phones; mobile technologies